A model of factor analysis: Reasons for using a helmet in a sample of non-competitive Italian cyclists. (October 2018) - Ferraro, Ottavia E.; Orsi, Chiara; Montomoli, Cristina; Morandi, Anna
Highlights: A greater helmet use among Italian men than women was found. Men more frequently use helmets out of habit and find the same among fellow cyclists. For women, motivation not to use a helmet is the perception of discomfort. In the North, a helmet is perceived uncomfortable to a greater extent than in the South. Cyclists who are helmet enthusiasts perceive the helmet as a safety benefit. Abstract: Introduction: The increased bicycle use for transport as an alternative to motorized vehicles has by now become a common occurrence in all Italian cities. Even though the benefits of using a helmet to protect against trauma in bicycle accidents have been demonstrated, its use is still limited. The objective of this study is to analyse those motivations for helmet wearing that can influence their adoption. Methods: Data was gathered through an online questionnaire in collaboration with the Federazione Italiana Amici della Bicicletta (Italian Federation of Friends of the Bicycle), a recreational cyclists association. Motivations to use a helmet were investigated using a factorial analysis model. Factors were analysed through a points allocation system and compared according to gender, area of residence and whether the cyclist was a helmet-enthusiast. Results: The sample was made up of 1781 individuals, with a declining participation rate from North to South; 63% of respondents were men. Three factors were identified from the sample: helmet use as a safety benefit; helmets being perceived as a hindrance; and helmet used out of habit as well as to follow the virtuous example of friends and/or acquaintances during cycling outings. The major kinds of evidence are: regarding gender, differences in the perception of a helmet as a hindrance (p < 0.001) and its use out of habit (p < 0.001); as for area of residence, differences in the perception of a helmet as a hindrance (p = 0.01) and its use out of habit (p < 0.01); as regards being a helmet-enthusiast, differences were found for all the factors (p < 0.01). Conclusions: These results contribute to understanding the scenario that affects motivational beliefs through facilitating or deterring cyclists from using a helmet during recreational cycling. The evidence suggests how to argue the helmet use discussion among Italians. In such a homogeneous population of respondents in terms of passion for cycling, opinions on helmet use were dissimilar from the point of view of both its perception and the subsequent motivation for using it. Exploring perceptions and motivations on helmet use is a key element in understanding cyclists' behaviour in order to characterize different users. A combination of friends/peer influence, reduction in the perception of helmets as a hindrance, and reinforcing of safety could represent the starting point for planning interventions.